皮膚病変を伴わないStevens-Johnson 症候群の1例 - 藤井, 仁; 伊藤, 広貴; 福岡, 佳昌; 小栗, 崇; 嘉悦, 淳男; 石井, 興 (日本口腔外科学会雑誌, 2023)
Stevens-Johnson syndrome (SJS) is a severe drug eruption that presents with fever, along with erythema, blisters, and erosion on the skin, oral cavity, eye conjunctiva and vulvar mucosa. Here we report a case of SJS without skin lesions in an 81-year-old man who underwent a tooth extraction at our department due to periodontitis. He developed a fever and swelling of the eyelids and lips during the night and visited our department because the symptoms had worsened. Upon examination, hyperemia of the bulbar conjunctiva and erosion in the oral cavity were observed, but no skin lesions were found. SJS was suspected by the dermatologist, and steroid therapy was started during hospitalization. Histopathological findings from a biopsy of the lip mucosa revealed necrotic changes in the epidermis, leading to a definitive diagnosis of SJS without skin lesions. A drug-induced lymphocyte stimulation test (DLST) was positive for acetaminophen, identifying the causative drug. When oral mucosal erosion with fever and eye symptoms such as and bulbar conjunctivitis is observed after the prescription of antibacterial drugs and antipyretic analgesics, drug-induced SJS should be suspected, even in the absence of skin symptoms, and a specialist should be consulted early. Furthermore, a biopsy analysis of the oral mucosa should be performed.